The management of coma. (February 2017) - Cooksley, Tim; Holland, Mark
Abstract: Coma is a medical emergency that can challenge the diagnostic and management skills of any clinician. A systematic and logical approach is necessary to make the correct diagnosis, the broad diagnostic categories being neurological, metabolic, diffuse physiological dysfunction and functional. Even when the diagnosis is not immediately clear, appropriate measures to resuscitate, stabilize and support a comatose patient must be performed rapidly. The key components in the assessment and management of a patient, namely history, examination, investigation and treatment, are performed in parallel, not sequentially. Unless the cause of coma is immediately obvious and reversible, help from senior and critical care colleagues is necessary. In particular, senior help is needed to make difficult management decisions in patients with a poor prognosis.